Importance of the temperature in the interaction plant-geminivirus - Corrales Gutiérrez, Miguel Ángel; Rodríguez-Bejarano, Eduardo; Castillo-Garriga, Araceli (My University, 2017)
Introduction. Geminivirusare plant viruses that have circular single-stranded DNA (ssDNA) genome encapsidated in twinned quasi-icosahedral (geminate) virionsand are a serious threat to diverse economically important crops such as tomato, pepper and cassava. TYLCV (Tomato yellow leaf curl virus) belongs to the genus begomovirus which is by far, the largest of the seven genera in the family Geminiviridae and it is a pathogen that induces a devastating disease in tomato in the Mediterranean region. Cultured tomatoes are often exposed to a combination of extreme heat and infection with TYLCV and this combination leads to intense disease symptoms and yield losses.The impact of temperature over the interaction tomato- TYLCVhas been characterized (Ghandi et al., 2016) but these results seem to be contradictory to our findings. Objective. The main objective of this work is to improve our understanding of the impact that high temperature has in the interaction plant-geminivirus.Material and methods. Nicotianabenthamiana plants were infected with TYLCV and growth in a chamber at 21 ºC or at 35 ºC. The amount of virus, symptoms, plant height and number of leaves were monitored at 14, 21 and 28 dpi (days post-infection). Three biological replicates were performed, each containing 15 infected plants and 10 non-infected plants (mock). Results. No differences were observed between non-infected and infected plants at both temperatures, in plant height or in the number of leaves, but the amount of virus and the severity of symptoms were significantly reduced in plants at high temperature. Conclusions. We conclude that TYLCV yield decreases in N. benthamiana due to high temperature and ongoing experiments in tomato TYLCV-infected plants will let us determine the importance of this finding in an agronomical important crop and to compare our results with the published data.
Keywords: Enfermedades por virus; Geminivirus; High temperature